A continuous time economic growth model with time delays in environmental degradation. Issue 1 (2nd January 2019) - Ferrara, Massimiliano; Gori, Luca; Guerrini, Luca; Sodini, Mauro
Abstract: The aim of this work is to analyse the interplay between economic growth and environmental quality. Specifically, the article considers an economic growth model with optimising agents à la Ramsey where production negatively affects the environment. The novelty of this work is to assume that such a negative impact does occur with a certain time lag rather than instantaneously, as is commonly assumed in economic models. The existence of (discrete) time delays in this process may be a source of instability of the unique stationary equilibrium of the system and may cause the emergence of Hopf bifurcations.